Pengaruh Ukuran Pemerintah, Pendapatan Per Kapita Dan Leverage Terhadap Keteraksesan Internet Financial Report Oleh Pemerintah Daerah - Anugerah Akbar Anthony Putra; Efrizal Syofyan (Universitas Negeri Padang, 2020)
This study aims to analyze 1) How does the size of the government affect the accessibility of internet financial report by the Regency / City Regional Government in West Sumatra Province, 2) How does the income per capita affect the accessibility of internet financial report by the Regency / City Regional Government in the West Sumatra Province, 3) How does leverage affect the accessibility of internet financial report by Regency/City Governments in West Sumatra Province, 4) Does the size of the government, per capita income and leverage jointly affect the accessibility of internet financial report by Regency/City Governments in West Sumatra Province . The results of the study found variables of government size, per capita income and unaffected leverage on the accessibility of internet financial report by the Regency / City Regional Government in West Sumatra Province